Self-Determination of a Person and Moral Stereotypes - Rybakovienė, Vanzeta (Problemos, 1990)
The relation between morality, manifesting itself as inner determination of a person, and social stereotypes of conduct as well as principles of social justice is considered in the article. The two, it is said, are constantly getting into a conflict, which on its tum is immanent to social relations. One can see, that the dimension of free individual decision in moral conduct historically is increasing. Nevertheless, man never feels himself absolutely free from social moral principles and norms.